Σχεδίαση και υλοποίηση τετραφασικών ταλαντωτών ελεγχόμενων απο τάση σε τεχνολογία CMOS 40 nm - Δημόπουλος, Χρήστος (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Ηλεκτρολόγων Μηχανικών και Μηχανικών Υπολογιστών. Τομέας Επικοινωνιών, Ηλεκτρονικής και Συστημάτων Πληροφορικής, 2016)
Object of this thesis is the analysis and design of quadrature voltage controlled oscillators at high frequencies of the order of GHz. Quadrature-VCOs are circuits used in modern transceiver architectures for producing quadrature signals, i.e. signals having a phase difference of 90°with each other, and are usually found in a phase locked loop circuit. Initially, there is a general reference to oscillators and the oscillation criteria are mentioned. They are being analysed into mathematical background the two main categories of oscillators, the ring oscillators and LC oscillators. The thesis deals mainly with the LC oscillators and thus they are being analysed thoroughly and their various topologies are presented. Moreover, the mathematical model of voltage controlled oscillators is described and the main characteristics and the elements that are consist of. Specifically, a reference is made to varactors and integrated inductors and the models of phase noise in oscillators circuits is being studied.